Grave stuff: litigation with a London tomb-maker in 1421. - Saul, Nigel; Mackman, Jonathan; Whittick, Christopher (Historical Research, 2011)
The recent A.H.R.C.-funded project on 'Londoners and the law' has brought to light a case in the court of common pleas in which the executors of Sir John Dallingridge of Bodiam (d. 1408) sued a London mason, John Petit, for failure to deliver to their satisfaction a tomb monument commemorating the deceased knight. The greater part of the contract for the monument was rehearsed in the pleadings, and as a result valuable light is shed on the expectations of patrons and the workings of the market in tomb monuments. Today, at Bodiam castle there survives a mutilated fragment of an alabaster torso which, on the evidence of the heraldry, must have formed part of a tomb monument to Sir John Dallingridge. It is suggested that this alabaster effigy is the product of a different commission from the one given to Petit, and that after Petit's dismissal Dallingridge's executors went to a Midlands firm in search of a suitable replacement.